Selected legal problems of EEG biofeedback therapy under the Polish law - Nowak-Gruca, Aleksandra (Medicine, law & society, 2018)
The use of EEG biofeedback for therapeutic or healing purposes has its justification in modern research and recently one can notice the increasing popularity of this method. Possible threats which may be associated with improper training and EEG biofeedback therapy may result from error in the diagnosis or incorrect selection of the training protocol. The effectiveness of therapy depends largely on the efforts of the patient himself, however, the range of waves will be amplified or suppressed by diagnosticians and therapists. If during an EEG biofeedback, the correct neuronal signal is amplified or suppressed, this can have adverse effects. In Poland, there are no legal regulations regarding the acquisition of qualifications for conducting neurotherapy. Likewise, there are no indications as to which institutions have the right to assign appropriate powers to use this type of apparatus. The lack of legal regulations means that now everyone can practice neurotherapy. The article presents selected legal problems related to conducting EEG biofeedback therapy under law, especially under Polish regulations, including the problem of the responsibility of the therapist or trainer.
Keywords: EEG; medicinski pripomočki; nevroterapija; odziv; pacientovo soglasje; pravna odgovornost